2021
DOI: 10.3390/jcm10112398
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic Retinopathy and Hearing Loss: Results from the Fifth Korean National Health and Nutrition Survey

Abstract: We investigated the association between the severity of diabetic retinopathy (DR) and hearing loss based on vascular etiology. We used data from the Korean National Health and Nutrition Survey 2010–2012. Adults aged >40 years with diabetes were enrolled. Demographic, socioeconomic, general medical, noise exposure and biochemical data were used. Participants were classified into three groups: diabetes without DR, non-proliferative DR (NPDR), and proliferative DR (PDR); participants were also divided into two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…The potential role of microvascular diseases in the development of hearing loss, especially in middle-aged patients, can be considered. 46 The prevalence of concurrent visual and hearing impairment is reported to be 16.6% in adults aged 80 years and older. 47 The SHELTER study reported that those with dual sensory impairment had higher rates of clinical problems than those without sensory impairment.…”
Section: Discussionmentioning
confidence: 99%
“…The potential role of microvascular diseases in the development of hearing loss, especially in middle-aged patients, can be considered. 46 The prevalence of concurrent visual and hearing impairment is reported to be 16.6% in adults aged 80 years and older. 47 The SHELTER study reported that those with dual sensory impairment had higher rates of clinical problems than those without sensory impairment.…”
Section: Discussionmentioning
confidence: 99%